(3GdPNjQI aj abg GdeGdcjIs - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA cJGH GdCMHGS Hbhdg (B: (3ai eQVi GdehJ dCfg hUjI dhGQK aEfg TQc s
(3BNQgG (B:s
(3jfJgi HGdaUd GdKGfi ai GdefGRYGJ ef cJGH GdJQcI Hbhdg (B: (3heb cGf GdebQi YOdG LGRJ TgGOJg ai cd ehVY dCfg jQLY HgG Yf faSg ced GdLRA GdSGOS s
(3fSNI KGfjIs
(3jTJed Ydi HbjI cJGH GdCMHGS hcJH (B: (3GdhUGjG HbSejgG hGdbSeI hGdTaYI hGdhcGdI hGdJQcIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdabg GdeGdcjs